Best Answer

x2 + x + 1 = 0

∴ x2 + x + 1/4 = -3/4

∴ (x + 1/2)2 = -3/4

∴ x + 1/2 = ± √(-3/4)

∴ x = - 1/2 ± (i√3) / 2

∴ x = (-1 ± i√3) / 2

Study guides

☆☆

Q: What is the solution of x2 plus x plus 1 equals 0?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x2+24x+144 = 9 x2+24x+144-9 = 0 x2+24x+135 = 0 (x+9)(x+15) = 0 x = -9 or x = -15

x2 + 10x = 0 x2 + 10x + 25 = 25 (x + 5)2 = 25 x + 5 = +-5 x1 = 0 x2 =10

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0

x2 + 7x + 9 = 3 ∴ x2 + 7x + 6 = 0 ∴ (x + 6)(x + 1) = 0 ∴ x ∈ {-6, -1}

x2+7x+12=0 x2+7x=-12 x+Sqaure Root of 7x= 2(SQ Root Symbol)3

Related questions

x2 + 49 = 0 ∴ x2 = -49 ∴ x = 7i

x2+x-6=0 * * * * * Perhaps the solution you are looking for is: x2 + x - 6 = (x - 2)(x + 3) = 0; whence, x = 2 or -3.

x2+24x+144 = 9 x2+24x+144-9 = 0 x2+24x+135 = 0 (x+9)(x+15) = 0 x = -9 or x = -15

y = x2 + x = 0 x (X + 1) = 0 x = 0 is one solution x = -1 is the other

x2 plus 3x plus 3 is equals to 0 can be solved by getting the roots.

no

You should be able to look at this equation, or use the discriminant and know that there are no real roots.

x2 + 7x = 2x2 + 6 x2 - 2x2 + 7x = 6 -x2 +7x - 6 = 0 or alternatively x2 - 7x + 6 = 0

-2

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

x2 + 3x - 10 = (x + 5)(x - 2) ⇒ x = -5 or 2

No.